Mechanical characteristics and load-bearing effect of roadway anchorage composite carrier - Wensong Xu; Yaoyuan Zhang; Chao Wang; Xinwen Wu; Jibin Zhou (Scientific Reports)
Abstract Bolt support improves the stress state of the surrounding rock and forms an integral bearing structure inside the anchored surrounding rock. Therefore, it is of theoretical significance and practical application value to systematically study the mechanical mechanism and bearing characteristics of the anchorage composite carrier and elucidate the interaction mechanism between the bearing effect of the anchorage composite carrier and the stability of the roadway surrounding rock. In this paper, a mechanical model for the anchorage composite carrier is meticulously constructed through a fusion of theoretical analysis and advanced numerical simulation techniques. An in-depth exploration is conducted to elucidate the factors that significantly impact the bearing characteristics of the anchorage composite carrier. Specifically, the study examines the influence of supporting parameters, including bolt length, bolt diameter, bolt spacing, preload force, and roadway width, on both the effective formation and the thickness of the anchorage composite carrier. Based on the bearing effect of the anchorage composite carrier, aiming at the supporting problem of the cross-layer roadway (III811 interlocking roadway) in Luling Coal Mine of Huaibei Mining Co., LTD., the support technology application based on the bearing effect of the anchorage composite carrier is carried out, the support design scheme is optimized, the supporting effect is evaluated, and the evaluation method of the supporting effect and stability of the roadway is proposed. It is significant to apply support technology based on the bearing effect of anchorage composite carriers.